Software reliability control of airborne failure-free computers - Зеленков, A. A. (Proceedings of National Aviation University (archive), 2000)
Considered is the problem of software reliability control of up to date airborne failure-free computers of automatic management system, constructed on the basis of integral modular aircraft electronics technology during operation period. Described is the method of evaluation of probable software failure and serial calculating algorithm based on the determination of margins of software failures according to operational control data